CFD SIMULATION FOR AIRSPEED AND TURBULENCE VALIDATION IN MAIN DUCTING OF OFFICE BUILDING - Sabilly Handi Pradana; Deni Shidqi Khaerudini (Universitas Mercu Buana, Prodi S2 Teknik Mesin, 2022)
This paper focuses on the calculation of sizing ducting based on cooling load requirements the main ducting of office building following regulation airspeed requirements using American Society of Heating, Refrigerating and Air Conditioning Engineers (ASHRAE) and Computational Fluid Dynamics (CFD) simulations. The purpose of this research is to validate the airspeed and turbulence that occurs in the main ducting between manual calculations and CFD simulations. From the calculation, the cooling load requirement is 58.22 kW, for the cooling process an air flowrate of 7117 L/s is needed which is designed to pass through the main ducting in rectangular shape. The main ducting size uses 1200 mm x 500 mm at a speed of 12.7 m/s according to ASHRAE. Autodesk Inventor software is used for ducting modeling and Autodesk CFD is used for airflow simulation. CFD simulations are performed by applying boundary conditions and input parameters. The results showed that the velocity of the ducting design was suitable at 12.7 m/s with laminar flow. The ducting geometry must be designed aerodynamically to reduce the pressure drop which can cause the speed to increase so that it is outside the required limits. Thus, the CFD simulation results have verified the validity of manual calculations.